Volume 2B: Turbomachinery 2020
DOI: 10.1115/gt2020-14990
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Laminar-Turbulent Transition on a Low-Pressure Turbine Outlet Guide Vane

Abstract: This work presents an experimental and numerical investigation on the laminar-turbulent transition and secondary flow structures in a Turbine Rear Structure (TRS). The study was executed at engine representative Reynolds number and inlet conditions at three different turbine load cases. Experiments were performed in an annular rotating rig with a shrouded low-pressure turbine upstream of a TRS test section. The numerical results were obtained using the SST k–ω turbulence model and the Langtry-Menter γ–θ transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…The thick OGV oil-visualizations are presented in this paper. Similar visualizations for the regular OGV can be found in an accompanying paper [10].…”
Section: Flow Visualizationssupporting
confidence: 53%
See 2 more Smart Citations
“…The thick OGV oil-visualizations are presented in this paper. Similar visualizations for the regular OGV can be found in an accompanying paper [10].…”
Section: Flow Visualizationssupporting
confidence: 53%
“…It was found that the formation of this region is very sensitive to the oil-film thickness, which indicates that a laminar flow separation with further turbulent reattachment may take place. The accompanying study [10] shows that on the regular vane the laminar-turbulent transition of the boundary layer takes place in this location and that the transition occurs at strong negative values of the acceleration parameter close to the separation margin.…”
Section: Flow Visualizationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Jonsson et al extended these measurements to look at secondary flows [9] and heat-transfer [10] in more detail. Deshpande et al [11] and Jonsson et al [12] also studied surface roughness and laminar-turbulent transition in this TRS. Vikhorev et al [13] continued to experimentally investigate both thick vanes and engine mount bumps in this circular TRS.…”
Section: Introductionmentioning
confidence: 89%
“…The parts downstream of the OGV are modular and relatively simple and cost-effective to replace. Shroud, hub and ICDs can be replaced with instrumented geometries with pressure taps as in Jonsson et al [2018] or for heat transfer studies and local transition detection as in Jonsson et al [2020b] and Jonsson et al [2020c].…”
Section: Traverse Details and Special Instrumentationmentioning
confidence: 99%